Perspectives on waiting times in an antenatal clinic: A case study in the Western Cape - Justine C. Baron; Doreen Kaura (AOSIS, 2021)
Background: Antenatal care (ANC) is vital in reducing maternal and neonatal morbidity and mortality. Globally, 85% of women had one ANC visit with a skilled birth attendant and only 58% received the recommended four ANC visits. Long waiting times (LWTs) in the antenatal clinic affects the utilisation of the service. Long waiting times are viewed as a significant barrier to ANC utilisation and needs further investigation. Aim: The aim of this study was to explore and describe the contextual realities within the antenatal clinic that influenced waiting times (WTs). Setting: This study was conducted in an antenatal clinic, within a Midwife Obstetric Unit (MOU), Western Cape, South Africa. Methods: This study utilised a qualitative methodology with a single case study design with three embedded units of analysis. Purposive sampling was used to recruit the participants. Data were collected through unstructured observation and semi-structured interviews with pregnant women and midwives. Interviews were audio recorded, transcribed and analysed using the framework method. Results: The antenatal clinics had LWTs. The barriers to WTs were related to staff factors, patient factors, operational factors, communication, equipment and infrastructure and other research participant recruitment. Conclusion: The factors that influenced WTs are multifaceted and interrelated. Many of the factors influencing the WTs could be remedied by implementing appropriate workflow strategies, improving communication and increasing equipment availability. The findings can be used to develop waiting time guidelines and improve WTs in the antenatal clinic.